Evaluation of Nutritional Quality and Organoleptic Properties of Soy-poundo Yam Flour - , J. I. Okoye; , J. I. Nwodo; , S. I. Eze (Archives of Current Research International, 2024)
This study was designed specifically to evaluate the nutrient composition and sensory properties of soy-poundo yam flours produced from white yam and soybean flours. The white yam tubers and soybean seeds were processed into flours and blended in the ratios of 100:0, 90:10, 80:20, 70:30, 60:40 and 50:50, respectively and used to produce soy-poundo yam flours with 100 % instant yam flour used as control. The samples of soy-poundo yam flour produced were evaluated for nutrient composition and sensory properties using standard methods. The moisture, crude protein, fat, ash and crude fibre contents of the samples increased significantly (p<0.05) with increase in substitution of soybean flour from 7.56 - 8.36%, 4.41 – 21.14%, 4.18- 5.09%, 2.51- 4.16% and 2.76 - 4.06%, respectively, while their carbohydrate and energy contents decreased from 78.74-57.21% and 370.16- 359.15KJ/100g, respectively. The mineral composition of the samples revealed that the potassium, magnesium, manganese, iron, zinc and copper contents of the products ranged from 78.34 – 164.11mg/100g, 2.46 -17.14mg/100g, 20.48 -125.53mg/100g,1.56 -2.23mg/100g, 1.78 -263mg/100g and 2.88 – 3.64mg/100g, respectively. The vitamin content of the samples showed that the vitamin A, pyridoxine, ascorbic acid, thiamine, vitamin E and niacin contents ranged from 12.00-12.70mg/100g, 2.28-2.59mg/100g, 16.1-17.07mg/100g, 56.07- 74.46mg/100g, 3.34-4.10mg/100g and 2.29 -3.22mg/100g, respectively with the control sample having the least values for all the vitamins evaluated. The sensory properties of the soy-poundo yam flour doughs obtained upon reconstitution of the samples with boiling water also revealed that the colour, taste, texture and aroma of the control sample (Poundo yam prepared from 100% instant yam flour) were the most acceptable to the assessors compared to the samples prepared from the substituted samples. Although the poundo yam dough made from the control sample was the most acceptable, the other test samples prepared from soy-yam composite blends were equally acceptable based on their relatively high scores in all the sensory attributes evaluated by the judges. The study, therefore, showed that the enrichment of yam flour with soybean at different graded levels would not only improve the nutrient contents of soy-poundo yam flour but would also add varieties to poundo yam meal due to improvement in its colour and texture.